What School Psychologists Should Know About Multiple Sclerosis - Phillips, Ashley N.; Maricle, Denise E. (Journal of the American Academy of Special Education Professionals, 2021)
Multiple sclerosis is an inflammatory autoimmune disease that attacks the central nervous system through the destruction of myelin. Frequently cited symptoms include cognitive impairment as a hallmark repercussion, neuropsychological executive dysfunction, and psychosocial disturbances, such as affective disorders and fatigue. Other symptomatology includes physical deficits, language delays, increased school absenteeism and dropout rates, and diminished academic achievement. MS is primarily observed in young adults, between ages 20 to 40 years; however, 3% to 10% of all individuals with an MS diagnosis experience the onset of this disease before age 18. With the etiology of MS still unclear and its manifestation and progression unpredictable, interventions and supports must be frequently evaluated by a treatment team to ensure continued effectiveness for the individual’s cognitive and physical abilities, language development, and psychosocial needs. Additionally, the caregivers and family of the child or adolescent with MS should be incorporated when serving the child.